Current challenges on the widespread adoption of new bio-based fertilizers: insights to move forward toward more circular food systems - Álvarez Salas, Mario; Sica, Pietro; Rydgård, Maja; Sitzmann, Tomas Javier; Nyang’au, Jared Onyango; El Mahdi, Jihane; Moshkin, Egor; de Castro e Silva, Hellen Luisa; Chrysanthopoulos, Stamatis; Kopp, Clara; Wali, Khan; Zireeni, Yusra; et al. (Frontiers in Sustainable Food Systems, 2024)
To meet global food demands sustainably, it is necessary to safeguard finite natural resources and reduce harmful emissions to the environment. Nutrients in biowastes are often not managed appropriately. Instead, they can be recovered, recycled into bio-based fertilizers (BBFs) and reincorporated into food production systems. This review addresses three critical issues for developing and adopting new BBFs, focusing on the European context: 1) BBFs should match the agronomic efficiency of mineral fertilizers.We propose that the agronomic efficiency of BBFs can be increased through pre-treating the inputs in biowaste transformation processes (e.g. anaerobic digestion), chemical treatments of existing BBFs, organo-mineral combinations, and soil placement strategies. 2) Production and use of new BBFs is not free of environmental impacts, and these are influenced by regional conditions. 3) Public perception and end-user preferences play a significant role in the adoption of BBFs. Therefore, it is vital to address the requirements of end-users of BBFs Our findings indicate that for widespread adoption, BBFs need sufficient and reliable nutrient amounts and crop-adequate ratios, as well as competitive pricing. A key advantage of BBFs over mineral fertilizers is their ability to improve soil fertility. However, farmers also require fertilizers that can be handled and applied with existing machinery and offer the practicality of commercial products. Another important aspect is the willingness of consumers to buy products fertilized with BBFs.Designing and promoting BBFs requires a careful assessment of environmental impacts and regional conditions, as the sustainability of BBFs depends on factors like energy sources and biowaste transport distances. Ultimately, the goal is to promote a circular economy and not just to substitute mineral fertilizers with new products. This review aims to guide researchers, policymakers, and stakeholders by highlighting key innovations and addressing critical barriers.